2022
DOI: 10.1101/2022.01.25.477549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Live biotherapeutic throat spray for respiratory virus inhibition and interferon pathway induction

Abstract: Respiratory viruses such as influenza viruses, respiratory syncytial virus (RSV), and coronaviruses initiate infection at the mucosal surfaces of the upper respiratory tract (URT), where the resident respiratory microbiome has an important gatekeeper function. In contrast to gut-targeting administration of beneficial bacteria against respiratory viral disease, topical URT administration of probiotics is currently underexplored, especially for the prevention and/or treatment of viral infections. Here, we report… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
(58 reference statements)
2
4
0
Order By: Relevance
“…The second major finding of our work is the lower number of virus-positive test results at day 21, in line with the selected antiviral mode of action in vitro, where we showed that the selected lactobacilli could induce interferon regulatory pathways and reduce the cytopathic effects of coronaviruses and related respiratory viruses in cellular models (24). Due to the delay between testing and inclusion, most participants started within 2 to 5 days after the onset of their first symptoms, when the viral loads were the highest.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The second major finding of our work is the lower number of virus-positive test results at day 21, in line with the selected antiviral mode of action in vitro, where we showed that the selected lactobacilli could induce interferon regulatory pathways and reduce the cytopathic effects of coronaviruses and related respiratory viruses in cellular models (24). Due to the delay between testing and inclusion, most participants started within 2 to 5 days after the onset of their first symptoms, when the viral loads were the highest.…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, the probiotic definition is not limited to the gut ( 23 ). We have recently developed an antiviral throat spray with three Lactobacillaceae strains that were selected based on their safety, their in vitro multifactorial modes of action on key aspects of viral infection and disease (including interferon activation and blocking of upper respiratory tract [URT] viral infection), and their ability to thrive in the human respiratory tracts of healthy volunteers ( 24 ). Yet microbiome therapy in patients with live bacteria has several challenges, such as formulations, regulation, and selection of the target patient population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results on the viral loads at day 21 are promising and in line with our previously reported in vitro data, where we showed that the microbiome members that were selected for the throat spray show clear antiviral effects against coronaviruses under controlled in vitro study set-ups [16]. In the trial with the oral probiotic L. plantarum strains and Pediococcus acidilactici KABP021, a significantly larger reduction in nasopharyngeal viral load was observed in the verum group at day 15 and day 30 (p < 0.001) [8].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the probiotic definition is not limited to the gut [15]. We recently developed a microbiome-modulating throat spray with three Lactobacillaceae strains that were selected based on their safety and in vitro multifactorial modes of action on the key aspects of viral infection and disease, and their ability to thrive in the human respiratory tract of healthy volunteers [16]. Yet, microbiome therapy with live bacteria has several challenges, such as formulation and selection of target patient population.…”
Section: Introductionmentioning
confidence: 99%